2013
DOI: 10.3389/fonc.2013.00204
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Enhancement of Drug Penetration in Solid Tumors

Abstract: Increasing the penetration of drugs within solid tumors can be accomplished through multiple ultrasound-mediated mechanisms. The application of ultrasound can directly change the structure or physiology of tissues or can induce changes in a drug or vehicle in order to enhance delivery and efficacy. With each ultrasonic pulse, a fraction of the energy in the propagating wave is absorbed by tissue and results in local heating. When ultrasound is applied to achieve mild hyperthermia, the thermal effects are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 120 publications
0
24
0
Order By: Relevance
“…Ultrasound is known to promote membrane permeability, thus increasing intracellular drug accumulation. Previous studies have suggested that the mechanisms by which ultrasound enhances the cytotoxicity of chemotherapy drugs include increased generation of reactive oxygen species [10,11], intracellular drug accumulation [12,13], and cell membrane permeability [14,15,16]. The combined therapy concentration and sufficient exposure time were crucial to the chemotherapeutic efficacy in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Ultrasound is known to promote membrane permeability, thus increasing intracellular drug accumulation. Previous studies have suggested that the mechanisms by which ultrasound enhances the cytotoxicity of chemotherapy drugs include increased generation of reactive oxygen species [10,11], intracellular drug accumulation [12,13], and cell membrane permeability [14,15,16]. The combined therapy concentration and sufficient exposure time were crucial to the chemotherapeutic efficacy in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Several good reviews on the use of HIFU in nanoparticle drug delivery have been published [27, 103105]. Ultrasound technology can impart both thermal and mechanical effects to improve liposome drug delivery.…”
Section: Current Strategiesmentioning
confidence: 99%
“…The prolific tumor-responsive liposome literature is beyond the scope of this article but has been recently reviewed [2123]. A different strategy highlighted in this article is the use of liposome formulations responsive to external stimuli (hyperthermia, radiofrequency ablation, ultrasound, magnetic field, and radiotherapy) [3, 2127]. By applying an external stimulus to the local tumor region, the liposomes located within the tumor are triggered to release their drug payload.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion through skin may be enhanced by sonophoresis (phonophoresis), electrophoresis (iontophoresis), external pressure, and massage [20,[41][42][43][44][45][46]. The major advantage of these methods is considerable reduction of treatment time from hours down to several ten minutes [41,[47][48][49][50][51][52][53][54][55][56]. Skin optoporation based on fractional tissue ablation with pulsed lamp or Er:YAG laser radiation was reported to considerably enhance epidermal permeability for OC agents and nanoparticles [57][58][59].…”
Section: Introductionmentioning
confidence: 99%